PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK GULA AREN MEREK ARENTA NUSANTARA DI MUNJUL KABUPATEN PANDEGLANG - Zahra, Surti; Tabroni, Tabroni; Tunavisa, Zakia (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This study aims to examine the influence of brand image and price on the purchasing decisions of Arenta Nusantara brand palm sugar in Munjul, Pandeglang Regency. Using a quantitative approach with descriptive techniques, this research involved 53 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that both brand image and price have a significant positive effect on purchasing decisions, both partially and simultaneously. Brand image and price collectively explain 82.9% of the variation in purchasing decisions. These findings highlight the importance of maintaining a strong brand image and implementing appropriate pricing strategies to influence consumer purchasing decisions in the local palm sugar market